A friend indeed to friends in need? China's trade regime and Covid-19 vaccine diplomacy - Indra de Soysa; Krishna Chaitanya Vadlamannati (China Economic Quarterly International)
Employing newly available data on Chinese Covid-19 vaccine deliveries for a cross-section of 157 countries, we examine if China's vaccine diplomacy is driven by altruistic, enlightened self-interested motives or by purely strategic motives. According to the enlightened self-interested logic, China's vaccine supply would coincide with helping countries dependent on China for trade, i.e. its trading friends, while the strategic logic would entail providing vaccines to countries important commercially to China. In other words, the gravity of the Covid situation would be leveraged by China for strategic gain. Utilizing the logit estimator on probability of receiving vaccines from China and Tobit estimator on vaccine purchases and donations, we find that developing countries that are important to China's trade, and thereby, China's own commercial interests were less likely to get vaccines compared with countries that are more dependent on China. Furthermore, we find that countries more dependent on China are also likely to receive vaccine donations rather than purchases, suggesting that vaccine diplomacy was unlikely to be for commercial and strategic gain. Our results taken together signify that vaccine deliveries by China were not manipulated by trade interests in Beijing. The results suggest instead that China supplied vaccines to countries needing them and with whom Chinese goodwill reflects a more normal course of diplomacy—to service friends in need.